Optimizing Patient Flow And Care Pathways In Medical Departments: A Systematic Review Of Process Improvement Strategies, Technologies, And Outcomes (The Review of Diabetic Studies, 2025)
This systematic review explores strategies, technologies, and organizational approaches aimed at optimizing patient flow and care pathways in medical departments. Inefficient patient flow remains a persistent challenge in healthcare systems, leading to increased waiting times, overcrowding, reduced quality of care, and higher operational costs. This review synthesizes evidence from recent studies (2016–2025) focusing on process improvement methodologies such as Lean, Six Sigma, and workflow redesign, alongside digital health solutions including electronic health records, artificial intelligence, and telemedicine. Following PRISMA guidelines, relevant studies were identified, screened, and analyzed based on predefined criteria. The findings demonstrate that integrated approaches combining process optimization and digital technologies significantly improve patient throughput, reduce length of stay, and enhance patient satisfaction. The review highlights the importance of multidisciplinary collaboration and knowledge management in sustaining improvements and concludes that a holistic, patient-centered framework is essential for optimizing healthcare delivery.